Improving the Lexicographic Database of Agricultural Thesaurus in Languages (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article examines the concepts of agrarian coastal thesaurus, thesaurus lexicography and terminology. It also analyzes the thesaurus expression of agricultural terminology in the Russian and Uzbek language materials in the agrarian terminological thesaurus and terminological databases.